ANALISIS RESOURCE BASED VIEW (RBV) PADA MIROTA BATIK (HAMZAH BATIK) PUSAT BATIK DAN KERAJINAN, YOGYAKARTA - , Citra Dewi Mariana ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The company has a number of unique resources, this is what distinguishes a company with other companies. Companies that have and use resources and capability efficiently have a greater opportunity to operate economically and better satisfy customers. Thus, to be able to maintain superior performance of companies in an industry, then a company should be protected by the factors that could make it difficult to imitate by competitors. Resource Based View appeared to study these factors, and basing his thinking on the view that any company basically has a fundamental difference because it has a unique set of resources. This study aims to analyze the internal environment of Mirota Batik (Hamzah Batik) Centre of Batik and Handicraft Yogyakarta through the resource based view approach to determine the resources and capabilities that set them apart from its competitors through the analysis of the value chain (value-chain analysis) and in order to achieve sustainable competitive advantage using the VRIO ( Valuable, Rarity, Imitability, Organization) Framework. The results showed that the resources and capabilities Mirota Batik is competitive parity, temporary competitive advantage, and sustained competitive advantage.